An empirical analysis of double reduction education policy based on public psychology - Zhang, Xin; Zhao, Weibin; Zhou, Kai (Frontiers in Psychology, 2022)
At present in China's double reduction policy implementation, the public opinion of the current education system remains a certain degree of difference, in order to explore double reduction policy under the implementation of the public opinions on all aspects of the psychological education system, Firstly, the research collected the data of the public's views on education concept under the implementation of the double reduction policy through questionnaire survey, Then, SPSS software was used to analyze the difference of the public's educational concept data, and AMOS software was used to observe the public's psychological concept of education in all aspects under the implementation of the double reduction policy, and the corresponding structural model equation was established, so as to obtain the public's psychological view of education under the implementation of the double reduction policy, to provide corresponding educational psychological suggestions for the construction of later education system.